The effects of repeated mild stress on a transgenic mouse model of Alzheimer's disease - Rattray, Ivan (2010)
Alzheimer's disease (AD), the most common form of dementia, is a devastating age-related neurodegenerative disorder. There is a growing body of evidence suggesting that leading a stressful lifestyle is associated with a heightened risk of developing AD. This is supported by preclinical evidence using transgenic mice over-expressing genetic mutations leading to overt ß-amyloid protein production, a pathological marker of AD; stress in such mice has been capable of exacerbating AD-associated pathologies, including accelerating memory impairments and elevating ß-amyloid levels. In contrast, a recent study from our group demonstrated that a repeated mild stress procedure, novel cage stress, improved a short-term memory deficit and reduced the normal age-related increase in (3-amyloid levels. This thesis aimed to further characterise the beneficial effects of novel cage stress on AD-associated pathology in the TASTPM mouse model (double transgenic hAPP695swe x PS-I. M146V) which exhibits overt, age-related ß-amyloid pathology. First, age-related changes in AD- associated pathology, with or without exposure to novel cage stress, were assessed using a multidisciplinary approach incorporating measures of cognitive performance, in vivo magnetic resonance imaging and post-mortem analysis of ß-amyloid levels. The aim was to detect an age where we observe the most robust effect of stress; this time window was subsequently targeted to investigate a potential underlying mechanism, namely signalling though the glutamate alpha-amino-3-hydroxy-5- methyl-4-isoxazolepropionic receptor (AMPAr). Studies described throughout this thesis, alongside previously published data, indicate novel cage stress appears to improve AD-associated pathology in TASTPM mice, but independently of AMPAr function. It is likely that novel cage stress is insufficiently severe to induce detrimental effects, but, rather, subsequent repeated stimulation and physical activity may improve pathological status. A better understanding of lifestyle risk factors of AD, such as stress, will aid in identifying those at risk of developing the disorder. Moreover, discovering the underlying mechanisms linking stress with AD may open novel therapeutic avenues to treat the disorder.